2019
DOI: 10.1039/c8na00325d
|View full text |Cite
|
Sign up to set email alerts
|

An atom efficient, single-source precursor route to plasmonic CuS nanocrystals

Abstract: The synthesis of colloidal semiconductor nanocrystals (NCs) from single-source precursors offers simplified manufacturing processes at the cost of reduced atom efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…This is exemplified by a recent study of [Cu{S 2 CN(CH 2 CO 2 H) 2 } 2 ] which, unlike simple alkyl derivatives, has good water solubility, enabling self-capped copper-sulfide QDs to be generated in water. 36 A third type of DTC are those generated from primary amines. They are relatively easy to prepare, but the free ligands have a much smaller stability window than their disubstituted counterparts.…”
Section: Dithiocarbamates and Their Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is exemplified by a recent study of [Cu{S 2 CN(CH 2 CO 2 H) 2 } 2 ] which, unlike simple alkyl derivatives, has good water solubility, enabling self-capped copper-sulfide QDs to be generated in water. 36 A third type of DTC are those generated from primary amines. They are relatively easy to prepare, but the free ligands have a much smaller stability window than their disubstituted counterparts.…”
Section: Dithiocarbamates and Their Complexesmentioning
confidence: 99%
“…An increase of 15.1 °C was observed over 3 min, while the water control exhibited an increase of only 0.7 °C. 36 A second interesting recent development comes from Trindade and co-workers, who decomposed [Cu(S 2 CNEt 2 ) 2 ] and [Cu(S 2 CNBu 2 ) 2 ] at 240 °C in ionic liquids, obtaining digenite (Cu 9 S 5 ) nanocrystals as opposed to covellite, which was formed at the same temperature in OLA. 219 Ajibade and Botha have also reported that decomposition products of [Cu(S 2 CNBu 2 ) 2 ] in TOP/HDA are highly temperature dependent.…”
Section: Groupmentioning
confidence: 99%
“…Many variants have been prepared, examples of which are shown in Figure 2. The addition of substituents to the end of alkyl chains (Figure 2a) allows tuning of the water solubility (e.g., X = OH) [16,30,31] and acid-base properties (e.g., X = CO 2 H or NEt 2 ) [30,31].…”
Section: Copper(ii) Bis(dithiocarbamate) Complexesmentioning
confidence: 99%
“…Many variants have been prepared, examples of which are shown in Figure 2. The addition of substituents to the end of alkyl chains (Figure 2a) allows tuning of the water solubility (e.g., X = OH) [16,30,31] and acid-base properties (e.g., X = CO2H or NEt2) [30,31]. Beer and co-workers have synthesised a series of macrocyclic complexes containing two (Figure 2b) or three Cu(II) bis(dithiocarbamate) centres [32][33][34], some of which serve as selective anion receptors [32,33].…”
Section: Copper(ii) Bis(dithiocarbamate) Complexesmentioning
confidence: 99%
See 1 more Smart Citation